(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2023)
The Bali sardinella (Sardinella lemuru) from ’PPN Pengambengan’ in Bali Strait, Indonesia, has a high commercial value and is under pressure from fishing, despite the fact that the fish growing state is poorly understood. The goal of this study is to discover numerous elements of Bali sardinella growth, such as size distribution, length-weight relationship (LWRs), condition factors, and growth patterns. A total of 817 Bali sardinella fish with lengths ranging from 105-210 mm were sampled in order to determine the length-weight relationship (LWRs) and condition factors. Local fishermen primarily caught them with purse seines (mesh size 0.75 inch). According to the findings, the Bali sardinella (both female and male) growth allometrically (b=2.8656-2.9367), showing that the fish gets slimmer as it grows longer. There was no difference in the percentage of capture numbers between males and females, nor in the condition factor (k) (p>0.05). Male and female mean k values were 0.9672±0.0396 and 0.9912±0.0670, showing that the Bali sardinella are in good condition.